TINGKAT KEBUGARAN JASMANI ADAPTIF PADA ANAK ERKEBUTUHAN KHUSUS DI SLB NEGERI 3 LOMBOK TIMUR: PROFIL KESEIMBANGAN DAN KECEPATAN - Fauzilina Sani; Irna Ningsi Amalia Rachman; Erna Fitriatun (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
T Adaptive physical education is essential to support the physical fitness of children with special needs (CSN). This study aimed to describe the adaptive physical fitness profile of CSN at SLB Negeri 3 Lombok Timur using selected EUROFIT-based tests focusing on balance and speed. A quantitative descriptive design was employed. Thirty students were selected through purposive sampling from a population of 108. Balance was assessed using a Flamingo Balance Test (maximum 60 s), while speed was measured using a 50 m sprint (time in seconds). Raw scores were transformed into a 3–10 composite index using min–max normalization and categorized into good (7.67–10.00), moderate (5.33–7.66), and poor (3.00–5.32). Results showed that 33.3% of students were in the good category, 26.7% moderate, and 40.0% poor. In balance, the highest mean was observed in the hearing-impaired male group (48.70 ± 12.83 s), while the intellectual disability male group showed the lowest (26.40 ± 5.13 s). In speed, the hearing-impaired male group had the best (fastest) mean time (7.57 ± 0.82 s). The findings suggest that balance and speed training should be strengthened through structured adaptive physical education programs and periodic monitoring.